High-dose versus low-dose intravenous proton pump inhibitor treatment for bleeding peptic ulcers. (December 2012) - Leontiadis, Grigorios I; Howden, Colin W; Barkun, Alan N
Evaluation of : Liu N, Liu L, Zhang H et al . Effect of intravenous proton pump inhibitor regimens and timing of endoscopy on clinical outcomes of peptic ulcer bleeding. J. Gastroenterol. Hepatol. 27(9), 1473–1479 (2012). Peptic ulcer bleeding is a common medical emergency associated with significant mortality and healthcare costs. All recent guidelines agree on the beneficial role of proton pump inhibitor treatment, but there is still controversy regarding the optimal dose and route of administration of proton pump inhibitors. The evaluated article reports on a large, single-center randomized controlled trial that compared the clinical efficacy of a low-dose twice-daily intravenous bolus regimen with a high-dose continuous intravenous infusion regimen in 875 patients with acute bleeding from peptic ulcers. The high-dose regimen was associated with significant reductions in rebleeding, blood transfusion requirements and length of hospital stay. There was no demonstrable difference in mortality or the need for endoscopic hemostatic treatment or surgery. We discuss the strengths and limitations of the evaluated article, as well as the implications for clinical practice.